Engineering Properties of Steel Fiber Reinforced Self-Compacting Concrete (SFR-SCC) - Alrawashdeh, Anas A.A. (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
Self-compacting concrete (SCC) is a durable, highly flowable concrete with no tendency for segregation. It can easily fill complex formwork and passing through enclosing dense bars, and it consolidates without any need of vibration. SCC has the same brittle behavior as plain concrete, but this shortcoming can be eliminated by the inclusion of reinforcing fibers which carry tension forces and improve mechanical properties. This study investigates the effect of using steel fiber to reinforce self-compacting concrete and evaluate the improvement on physical and mechanical properties of the SCC matrix. For this purpose, six mixes of steel fiber reinforced self-compacting concrete (SFRSCC) were prepared with two different steel fiber aspect ratios of 60 and 80 l/d at three volume fractions (Vf ) of 0.35%, 0.45%, and 0.55%, in addition to a control mix. All samples were casted with constant w/b ratio 0.34 and 2% silica fume of cement content as additive. The experimental results indicated that adding hooked end steel fiber slightly affected the compressive strength, ultrasonic pulse velocity, and permeability. On the other hand, adding the fibers increased the flexural strength, toughness, split tensile strength, and impact resistance of SCC depending on aspect ratio (l/d) and volume fraction ( Vf ).

ÖZ: Kendiliğinden yerleşen beton (KYB), ayrışma eğilimi olmayan, dayanıklı, oldukça akışkan bir betondur. Karmaşık kalıpları kolayca doldurabilir ve ağır çubukları sarabilir ve herhangi bir titreşim gerektirmeden konsolide olur. KYB, düz beton ile aynı gevrek davranışa sahiptir, ancak bu eksiklik, gerilme kuvvetleri taşıyan ve mekanik özellikleri iyileştiren takviye elyafın dahil edilmesiyle ortadan kaldırılabilir. Bu çalışma, kendiliğinden yerleşen betonu güçlendirmek için kanca uçlu çelik elyaf kullanımının etkisini araştırmakta ve KYB matrisinin fiziksel ve mekanik özellikleri üzerindeki gelişmeyi değerlendirmektedir. Bu amaçla,%0,35,%0,45 ve %0,55'lik üç hacim oranında, 60 ve 80 olarak iki farklı çelik elyaf en boy oranıyla kontrol karışımına ek olarak altı çelik elyaf takviyeli kendiliğinden yerleşen beton karışımı hazırlanmıştır. Tüm numuneler sabit su/çimento oranı ve %2 silis dumanı ile dökülmüştür. Deneysel sonuçlar, kanca uçlu çelik elyafın eklenmesinin basınç dayanımını, ultrasonik ses hızını ve geçirgenliği az miktarda etkilediğini göstermiştir. Öte yandan, kanca uçlu Çelik elyafın betona eklenmesi, en boy oranına ve hacim fraksiyonuna bağlı olarak KYB'nin bükülme mukavemetini, tokluğunu, basmada yarma mukavemetini ve darbe direncini artırmıştır.
Master of Science in Civil Engineering. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Engineering, Dept. of Civil Engineering, 2021. Supervisor: Prof. Dr. Özgür Eren.
Keywords: Civil Engineering Department; Fiber-reinforced concrete--Building materials; Self-Compacting Concrete, Steel Fiber, Silica Fume, Mechanical Properties, Workability, Flexural Strength, Toughness, Impact Resistance, Durability.